Propriedades óticas e magneto-óticas de monocamadas de MoWSe2 - Rabahi, César Ricardo (2023)
Two-dimensional (2D) semiconductors, such as transition-metal dichalcogenide (TMD) monolayers, have attracted intense interest in the last years because of their direct band gaps, valley properties and excitonic effects. Particularly, TMD alloys with different compositions are interesting systems because of their band properties and possible applications in optoelectronics. Although spin-orbit engineering is already well known in monolayer TMD alloys, the valley Zeeman physics is still unexplored. In this work, we report on a detailed study of low temperature photoluminescence (PL) and magneto-photoluminescence under perpendicular magnetic field (up to 9 T) on a monolayer (ML) Mo0.5W0.5Se2 encapsulated with hBN. The nature of the emission peaks, the magnetic field dependence of polarization degree and g-factors are discussed in detail and compared with previous results in the literature. We have observed two bands in the PL spectrum. The higher energy band at around 1.69 eV was associated to possible contributions of bright and dark trions and phonon replicas of dark trions and the lower energy peak at around 1.61 eV was clearly associated to localized states. Particularly, the extracted g-factor of the trion emission peak showed a large value g≈ - 9.1 which are much higher than theoretical predictions for bright trions but is consistent with the values reported for dark states in the literature. Finally, our results suggest that TMD alloys are promising materials to explore fundamental physics and for possible application in optoelectronic devices.